Cultivating Commercial Agricultural Culture Among Rural Communities In East Malaysia Through Module Development (Journal of Namibian Studies : History Politics Culture, 2023)
Agricultural culture has become part of the cultural identity and livelihood of Malaysians.   However, the passage of time and the development of technology have transformed the persona of modern society who has developed the tendency of urbanization in earning a living in other sectors that are perceived to be more popular and provide the  desired outcomes compared to the agricultural sector. Ironically, the global mainstream reality coupled with the Covid-19 pandemic shows that Malaysia's economic landscape has increasingly been affected by the dependency on foreign countries and the devaluation of the country's imports in relation to food resources.  To cultivate a commercial agricultural culture in rural communities, particularly in Sabah, this interdisciplinary study focuses on the development process of three modules related to the cultivation, innovation, and marketing of an herb known locally as 'bawing."  Surveys, interviews and participant observation are used to collect both quantitative and qualitative data. The module development process is discussed based on the combination of the ADDIE and Sidek Module Development (SMDM) models.  These modules can be utilized to undertake the future knowledge transfer program and contribute towards the strategic planning or modus operandi of 'bawing' cultivation and commercialization.  Strengthening gardening or farming culture should be promoted especially among the youth to support human capital development, socio-economic enhancement and green sustainability to enjoy the nation's development in line with the policies of Shared Prosperity Vision 2030, Sustainable Development Goals 2020 (SDG2020) agenda and Sabah Maju Jaya Development Plan (2021-2025).